Optimisation of the CLIC baseline collimation system - Resta-López, J; Dalena, B; Schulte, D; Tomás, R; Seryi, A; Angal-Kalinin, D; Fernández-Hernando, J; Jackson, F (2010)
Important efforts have recently been dedicated to the improvement of the design of the baseline collimation system of the Compact Linear Collider (CLIC). Different aspects of the design have been optimised: the transverse collimation depths have been recalculated in order to reduce the collimator wakefield effects while maintaining a good efficiency in cleaning the undesired beam halo; the geometric design of the spoilers have also been reviewed to minimise wakefields; in addition, the optics design have been polished to improve the collimation efficiency. This paper describes the current status of the CLIC collimation system after this optimisation.